EFEKTIVITAS PROGRAM RUMAH BELAJAR UNTUK SDN 151 BENGKULU UTARA - Ghia Amanda Riska Pabela; Ismail, Kaifa; Rizky Agung Fambudi; Yola Maita Duri; Cristine Angelina Panjaitan; Anisya Citra Riski Apdillah; Kiki Amaliah (CV SWA Anugerah, 2024)
Penelitian ini mengevaluasi pelaksanaan dan efektivitas program